Social Inclusion-Based Library Promotion Strategy: An Analysis of Service Transformation at the Regional Library and Archives Office of South Sulawesi Province - Ramadayanti Ramadayanti (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2026)
This article examines a social inclusion–based library promotion model implemented at the Regional Library and Archives Office of South Sulawesi Province. The study aims to analyze the promotional strategies employed to support service accessibility for all segments of society and to assess their effectiveness in increasing user participation. The research adopts a descriptive qualitative approach using a case study method. The informants consist of librarians, administrative staff, and service users selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and subsequently analyzed using thematic analysis techniques. The findings indicate that promotional transformation is no longer oriented toward conventional information dissemination, but has evolved into a participatory promotion model grounded in social inclusion. This transformation is characterized by the integration of digital media, community collaboration, and the development of literacy programs that are responsive to the needs of vulnerable groups. Effective inclusion mechanisms include the use of social media as a platform for two-way interaction, the provision of accessibility facilities for persons with disabilities, the development of multilingual and audio-format collections, and the implementation of community needs based digital literacy programs. The main findings reveal a significant relationship between collaborative promotional strategies and increased user participation, as reflected in higher visitation rates, greater engagement in literacy activities, and improved public awareness of inclusive library services. Thus, promotional transformation functions as a strategic instrument in expanding access, fostering social engagement, and promoting the sustainability of inclusive library services. Abstrak Artikel ini membahas model promosi perpustakaan berbasis inklusi sosial di Dinas Perpustakaan dan Kearsipan Provinsi Sulawesi Selatan. Penelitian ini bertujuan untuk menganalisis strategi promosi yang diterapkan dalam mendukung aksesibilitas layanan bagi seluruh lapisan masyarakat serta menilai efektivitasnya terhadap peningkatan partisipasi pengguna. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Informan penelitian terdiri dari pustakawan, staf administrasi, dan pengguna layanan yang dipilih melalui purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi, kemudian dianalisis menggunakan teknik analisis tematik. Hasil penelitian menunjukkan bahwa transformasi promosi tidak lagi berorientasi pada penyebaran informasi secara konvensional, tetapi berkembang menjadi model promosi partisipatif berbasis inklusi sosial. Pola transformasi ini ditandai oleh integrasi media digital, kolaborasi komunitas, dan penyusunan program literasi yang responsif terhadap kebutuhan kelompok rentan. Mekanisme inklusi yang terbukti efektif meliputi pemanfaatan media sosial sebagai ruang interaksi dua arah, penyediaan fasilitas aksesibilitas bagi penyandang disabilitas, pengembangan koleksi multibahasa dan format audio, serta pelaksanaan program literasi digital berbasis kebutuhan masyarakat. Temuan utama penelitian ini menunjukkan adanya hubungan signifikan antara strategi promosi kolaboratif dan peningkatan partisipasi pengguna, yang terlihat dari bertambahnya kunjungan, keterlibatan dalam kegiatan literasi, serta meningkatnya kesadaran masyarakat terhadap layanan inklusif perpustakaan. Dengan demikian, transformasi promosi berperan sebagai instrumen strategis dalam memperluas akses, keterlibatan sosial, dan mendorong keberlanjutan layanan inklusif.